Acute Respiratory Distress Syndrome: Pathophysiology and Management - Darius Hartanto (PT Kalbe Farma Tbk., 2021)
Acute respiratory distress syndrome (ARDS) is a severe and fatal condition characterized by severe hypoxic respiratory failure resistant to oxygen therapy with bilateral lung infiltrates in radiological findings, first described in 1967 by Ashbaugh and colleagues. Several pathogenesis mechanisms were involved in ARDS, such as excess inflammation, endothelial permeability, epithelial permeability, and impaired alveolar fluid clearance. Kigali criteria as modified Berlin criteria typically maintain the previous criteria with removed PEEP requirement and hypoxemia evaluated using the ratio of arterial oxygen saturation by pulse oximetry/inspiratory oxygen fraction (SpO2/FiO2). Low tidal volumes and positive end-expiratory pressure (PEEP) were needed to prevent alveolar collapse due to loss of surfactant and fluid accumulation in alveoli. The prone position was shown to have a beneficial effect on a critically ill patient. Treatment should be aimed at the underlying condition even though lung injury has occurred in many cases. Acute respiratory distress syndrome (ARDS) adalah kondisi serius dan fatal yang ditandai dengan kegagalan pernapasan tipe hipoksia berat yang resisten terhadap terapi oksigen dengan infiltrat paru bilateral pada temuan radiologis; pertama kali ditemukan pada tahun 1967 oleh Ashbaugh dan kawan-kawan. Beberapa mekanisme patogenesis yang terlibat dalam ARDS adalah inflamasi berlebih, permeabilitas endotel, permeabilitas epitel, dan gangguan pembersihan cairan alveolar. Kriteria Kigali sebagai hasil modifikasi dari kriteria Berlin, mempertahankan kriteria sebelumnya dengan persyaratan PEEP dihilangkan dan hipoksemia dievaluasi menggunakan rasio saturasi oksigen arteri dengan oksimetri nadi/ fraksi oksigen inspirasi (SpO2/ FiO2). Volume tidal dan tekanan ekspirasi akhir positif (PEEP) rendah perlu untuk mencegah kolaps alveolar karena hilangnya surfaktan dan akumulasi cairan di alveoli. Posisi tengkurap terbukti memiliki efek menguntungkan pada pasien kritis. Pengobatan ARDS harus ditujukan untuk mengobati kondisi yang mendasarinya meskipun cedera paru telah terjadi dalam kebanyakan kasus.